A policymaking attempt to outlaw political dynasties - Cabochan, Gerardo V. Jr. (1991)
Greater democratization may be officially engineered through legislative policymaking. Thus far, three legislative attempts to strip Philippine politics of much of its elitist character have failed. The first attempt made by some delegates to the 1971 Constitutional Convention was stopped by the imposition of Martial Law. The second attempt made by the 1986 Constitutional Commission fell short of clear restrictions as it left the operational details of the law to a future legislature. And the third and most recent attempt by Congress never reached the conference committee level as the House of Representatives sat on its version of the antidynasty bill. The state policymaking process is stalled when the object of change is contrary to historical trends, prevailing cultural values and existing power arrangements.
Keywords: Political dynasties; Philippines -- Politics and government